Are two heads better than one? Challenges and prospects of chiefs and local government collaborative community development in Ghana. Issue 5 (20th October 2021) - Boateng, Kwabena; Bawole, Justice Nyigmah
ABSTRACT: In Africa, a dual political system is what characterizes the political landscape. Chiefs and officials of the central government collaborate to bring about development. Despite the transformation of the powers and functions of chiefs, they have constantly availed themselves to partner developmental agencies. The paper examined projects chiefs and local government authorities have initiated and the challenges that beset collaboration between the two agents of development. Purposive and simple random sampling techniques were employed to select 29 participants for this study conducted in the New Juaben in the Eastern Region of Ghana. Projects of collaboration included borehole and palace construction, provision of educational and health infrastructure, and footbridges. The collaboration between the stakeholders is fraught with challenges such as chieftaincy disputes, absentee chiefs, and land litigation. The paper recommends the formalization of the rotational system for selecting chiefs and noninterference by politicians in chieftaincy matters, to promote better collaboration.